Excited-State Relaxation Pathways of 4-Aminobiphenyl-2-Pyrimidine Derivatives: An Ultrafast Perspective - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M; Rojas-Figueroa, P (American Chemical Society, 2025)
Push-pull systems are key molecular architectures widely studied for their unique photophysical properties and tunable excited-state dynamics. Here, we present a systematic investigation of the influence of (i) solvent environment and (ii) donor-group substituents on the excited-state relaxation pathways and dynamics of two previously reported push-pull systems, namely 4-[4-(4-N,N-dimethylaminophenyl)phenyl]-2,6-diphenylpyrimidine and 4-[4-(4-N,N-diphenylaminophenyl)phenyl]-2,6-diphenylpyrimidine for D1 and D2, respectively. Previous findings demonstrated the presence of a twisted intramolecular charge transfer (TICT) state, which determined the fluorescent properties of D1 in highly polar solvents. However, this state was absent in D2 due to conformational constraints. By integrating steady-state emission mapping, time-correlated single photon counting (TCSPC), and femtosecond/nanosecond transient absorption spectroscopy (fs/ns-TAS), we are able to fully disentangle the complex landscape behind the excited state relaxation pathways in these push-pull systems both in nonpolar and polar solvents. Additionally, the correlation between multiple excited-state components and factors such as viscosity and solvent polarity is thoroughly rationalized. Altogether, these findings shed more light on the complex interplay between molecular conformation and solvent polarity in push-pull systems, which provides valuable insights into the rational design of advanced optoelectronic and photonic materials.